Migrant parent involvement: community, schools, & home - Vinton, Robert Deleon (Kansas State University, 2008)
This study focused on migrant parent involvement in the educational experience of their children. Specifically, the study investigated parent involvement in the domains of (1) Community Setting, (2) School Setting, (3) and Home Setting, and its relationship to student achievement in reading and mathematics assessments. Research has clearly indicated that parent involvement in the education processes of children is a critical facet to their academic success. Nevertheless, research has also indicated that parent involvement programming in educational institutions has been structured to address a stable, middle class, language and culturally homogeneous patron. Given the dynamics that impact migrant families, districts that are heavily impacted by migrant families must ameliorate parent involvement programming to address the unique needs of migrant families and their children. The participants in the study comprised 51 migrant families. The response rate for participation in the study consisted of 25% of the total migrant population within the school district. Data were gathered through a survey and an interview. Four research hypotheses were identified and tested. The procedure employed to test the strength of the relationship between the individual domains and the scores was the Pearson's Product-Moment Correlation. Additionally, a two-tailed test was used as the procedure for all hypotheses tested. The results indicated that there was not a significant relationship between the domains and student achievement scores. Nevertheless, there was variability among the students' achievement scores despite the level of involvement demonstrated by the parents. Therefore, based on the range of scores, student success was not predicated on the level of engagement that parents demonstrated on the survey. Other factors accounted for the academic success or failure of the student. These factors may have included constraints such as teacher training and dispositions, the level of second language development that the child possessed, and the resiliency of the student. Nevertheless, for students within the same family, where one student scored extremely high and the other child scored extremely low, parent involvement could have been the deciding variable that could have assisted the low scoring child succeed academically, if the parent training had taken into consideration the factors that impact migrant families.
Keywords: Parent Involvement; Barriers; Family advocacy; Education, Bilingual and Multicultural (0282); Education, Elementary (0524); Education, Guidance and Counseling (0519)